1994
DOI: 10.1002/bjs.1800810213
|View full text |Cite
|
Sign up to set email alerts
|

Audit of emergency preoperative resuscitation

Abstract: A total of 148 patients of mean age 61 years with acute gastrointestinal disease who were assessed as requiring preoperative resuscitation were studied. Overall, the mortality rate was 14.2 per cent and the morbidity rate 50.7 per cent. Resuscitation was associated with a mean(s.e.m.) improvement in predicted mortality rate of 4.2(0.8) per cent and in morbidity rate of 4.3(0.7) per cent. However, there was a group of patients in whom resuscitation was unsuccessful, despite there being no apparent difference in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 3 publications
0
15
0
Order By: Relevance
“…No vari-(text continues on p. 35 ables achieved statistical significance on multivariate analysis, although a low increase in PT showed the strongest association with mortality (P = .052).…”
Section: Efficacymentioning
confidence: 76%
“…No vari-(text continues on p. 35 ables achieved statistical significance on multivariate analysis, although a low increase in PT showed the strongest association with mortality (P = .052).…”
Section: Efficacymentioning
confidence: 76%
“…There is room for further research into whether improving the physiology score by resuscitation improves overall outcome after operation. McIlroy et al 10 reported that preoperative resuscitation could improve physiology scores and that outcomes were poor in patients who failed to respond to resuscitation.…”
Section: Pitfalls In Data Collection and Analysismentioning
confidence: 98%
“…A 12 part acute physiology score which included the patient's age, cardiac and respiratory history, blood pressure, pulse rate, Glasgow Coma Score, haemoglobin, leucocyte count, serum electrolytes and urea, and details of the most recent electrocardiogram were obtained preoperatively. A six part operative severity score was obtained immediately after surgery including operative severity, number of procedures, total blood loss, the presence of peritoneal soiling, the presence and extent of malignancy, and the timing of surgery [1,12–16]. These data were entered by the operating surgeon on a standardized proforma and collected centrally by a data clerk.…”
Section: Methodsmentioning
confidence: 99%
“…The POSSUM (Physiological and Operative Severity Score for the Enumeration of Morbidity and Mortality) system has been proposed as one method of standardizing data so that direct comparisons of patient outcomes can be made despite different patterns of referral and population characteristics [12–16]. The system importantly takes into account operative severity as well as patient physiological characteristics when assessing risk.…”
Section: Introductionmentioning
confidence: 99%